INFLUENCE DIVERSIFICATION PRODUCTS, PACKAGING INNOVATION, HALAL LABELIZATION TO INCREASING THE QUANTITY OF SALES OF BABAKAN SANDUBAYA BREAD - Hidayah, Nurul; Zulpawati; Atmayanti, Tati (IQTISHADUNA, 2023)
This study aims to analyze the effect of product diversification, packaging innovation, halal labeling on the sales quantity of Babakan Sandubaya bread. This type of research is a quantitative approach with asosiative method. The sample in a study amounted to 45. Data collection techniques using questionnaires and processed using SPSS 26. The results of this study indicate that partially product diversification has no positive and significant effect on the quantity of bread sales with the result that the t-count value (X1) is 0.200 which is smaller than the t-table value of 2.019 with a significance probability value of 0.842 > 0.05. Packaging innovation has a positive and significant effect on sales quantity with a t-count value (X2) of 6,437 greater than the t-table value of 2.019 with a significance probability of 0.000 <0.05. Halal labeling has a positive and significant effect on sales quantity with a t-count value (X3) of 2,383. greater than the t-table value of 2.019 with a significance probability of 0.004 <0.05. Meanwhile, simultaneously obtained an f-count value of 11.013 from f-table 2.83 and a significant probability value of 0.000 <0.05. So it can be concluded that the variables (X1), (X2), (X3) simultaneously have a significant effect on (Y) Babakan Sandubaya bread. Judging from the coefficient, the R square value is 0.69, this shows that out of 100% there are 69% of the independent variables that can explain the dependent variable. The remaining 31% is influenced by other variables not included in this study.